Pengaruh Strategi Kebijakan Pemulihan Ekonomi Nasional Terhadap Pasar Modal di Indonesia - Fajar Rachmandika Kurniawan; Pompong B Setiadi (Cakrawala Repositori IMWI, 2023)
Corona Virus Disease 2019 (Covid-19) has had enough impact on the Indonesian economy that an economic stimulus is needed that still prioritizes the safety and welfare of the people. The National Economic Recovery Program (PEN) was initiated to be a measure implemented to prevent the impact of the pandemic from being more severe. The purpose of this study is to describe the influence of the Covid-19 pandemic on the national economy, especially the condition of the capital market in Indonesia, describe the National Economic Recovery Program (PEN) as an effort to secure and restore the Indonesian economy and the effect of the program on the capital market in Indonesia. This research methodology uses a qualitative approach with case study analysis. The results showed that the PEN Program succeeded in maintaining the impact of the Covid-19 pandemic so that Indonesia's economic conditions, although affected, were relatively less severe than other countries. PEN also provides a positive stimulus to the capital market in Indonesia as indicated by the increase in the JCI level along with the stages of PEN implementation to date.